Analysis of Insurance Customer Factors to Renewal Using Hybrid AHP-FTOPSIS - Kwardiniya Andawaningtyas; Evi Ardiyani; Corina Karim (Cauchy: Jurnal Matematika Murni dan Aplikasi)
Human life is full of uncertainty that has enormous risks. Insurance is a one of methods that can help humans reduce those risks. Human needs for insurance causes competition among insurance companies in Indonesia to become very competitive. One factor that makes insurance companies to compete is to have its customers who make insurance renewals. Thesis discusses analysis of factors that influence insurance renewal using Analytical Hierarchy Process (AHP) method and the ranking of customer’s favorite insurance for renewal using the Fuzzy Technique for Order Preference by Similarity to Ideal Solution (FTOPSIS) method. Five criteria have been determined with each criterion having subcriteria in this study. AHP method is used to calculate the weight of criteria and to determine the factors that influence customers the most to do renewal. The  FTOPSIS method is used to determine the best alternative. The results of the analysis using these methods conclude was the main factor that influences the customers in conducting renewals is feature with the subcriteria of health protection needs. Meanwhile, the ranking of customer’s favorite insurance in conducting renewal is Takafulink Salam Cendikia with proximity coefficient value of 0,645, Takaful Al-Khairat with value 0,563, Takaful Dana Pendidikan with value 0,552, and Takafulink Salam with value 0,341